The impact of COVID-19 on supply decision-makers: the case of personal protective equipment in Spanish hospitals - Manuel F. Morales-Contreras; Marcelo Leporati; Luciano Fratocchi (BMC, 2021)
Abstract Background The COVID-19 pandemic has been recognized as a trigger for redefining supply chains at the global level, and has created an intense debate within the academic community and among policy-makers and practitioners. Among other industries, health care has been dramatically hit by the scarcity of "medical products," specifically for personal protective equipment (PPE-like), due to supply chain disruptions coupled with dramatically increased demand. We aimed to analyze how the scarcity of PPE-like during the COVID-19 pandemic has modified the behavior of decision-makers in the PPE-like supply chain at the hospital level, and to explore what changes could be implemented to cope with future PPE-like shortages. Methods We used an explorative approach based on semi-structured interviews with key informants in the Spanish health care industry. More specifically, we held interviews to industry experts at three hospitals in three Spanish regions to map the consequences of the COVID-19 pandemic onto the buying decision-making process. Results Different strategies were developed by decision-makers at hospitals before, during, and after the first wave of the COVID-19 pandemic in Spain. Our paper offers two main findings: a) decision-makers changed their purchasing behavior from a cost main driver to guaranteeing the availability of supplies; b) they supported the idea of giving more "strategic autonomy" to Spain or Europe through back and nearshoring decisions. Conclusions This paper could be of interest to health care management at the national, regional, and hospital levels, as well as for policy-makers, since it could help to establish and configure policies to support the sourcing of medical products (specifically PPE-like) to anticipate potential supply disruptions. Our paper contributes to the limited existing literature on how purchasing strategies at the decision-maker level and supply vary in the health care industry when a public health crisis appears, and what potential solutions might be for policy-makers and practitioners involved in the health care industry.